PENDEKATAN SUFISTIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - A. Qomarudin Qomarudin (STAI Ma'had Aly Al-Hikam Malang, 2019)
Education has the main goal to develop the all potentials of human beings, including; intellectual, emotional and spiritual. The problems that arise from the education such as fights, killings, brawls between students, and so on, certainly cannot be separated from the dry taste in the knowledge that has been obtained. So it is important in this case to discuss the spiritual side which is one part of intelligence possessed by humans through the Sufistic approach as a step in developing Islamic religious education learning. The sufistic approach in learning of Islamic education can be done through riyadlah (mental exercises) gradually with taking into the students condition. The process of riyadlah can be done by carrying out some material in Sufistic learning, which includes moral sufistic (tasawuf akhlaqi), practice sufistic (tasawuf amali), and philosophical sufistic (tasawuf falsasi).